Association between Angiographic Severity of Coronary Artery Disease and Erectile Dysfunction due to Internal pudendal Artery Stenosis - Hosen, Md. Imam; Al-Amin, Md.; Islam, Md. Tafijul; Shadly, Tausif Amim; Hasan, Md Zahid; Kabir, Md. Khairul; Ghose, Sujan; Rahman, Nazia (Cardiology and Cardiovascular Medicine, 2026)
Background: Erectile dysfunction (ED) is common in patients with coronary artery disease (CAD). As atherosclerosis is the common mechanism for vasculogenic ED and CAD, so there might be a correlation between these two. Objective: To find out the association between angiographic severity of coronary artery disease and ED due to internal pudendal artery (IPA) stenosis. Methods and Materials: This cross-sectional observational study was conducted at the Department of Cardiology at National Institute of Cardiovascular Diseases (NICVD), Dhaka among purposively sampled patients who had CAD on CAG & had ED on IIEF 5 questionnaire. A total 60 patient were divided in two groups depending on Gensini score being Gensini score < 20 in Group I and Gensini score ≥ 20 in Group II. Internal pudendal angiography was done in same settings following CAG. Correlation between Gensini score & significant IPA stenosis between two groups was done. Results: The mean IIEF 5 score was 14.8 ± 3.83 being lower in group II (15.93 ± 3.14 vs 13.67 ± 4.17, p=0.021). Significant IPA stenosis (> 50%) was more common in group II (20% vs 43.3%, p=0.042). Spearman’s rank correlation showed moderate negative correlation between Gensini score and IIEF 5 score (Spearman’s ρ = -0.475, p=0.01). Spearman’s rank correlation betwwen Gensini score & IPA atenosis showed moderate positive correlations (Spearman’s ρ = 0.410, p=0.03). Multivariate logistic regression analysis revealed severe coronary artery stenosis (Gensini score more than ≥ 20) and DM were the risk factor for significant IPA stenosis with OR 9.13 and 4.75, respectively. Conclusion: Angigraphic severity of coronary artery disease is positively correlated with ED due to IPA stenosis.